Variación de la robustez física de Sceloporus torquatus (Sauria: Iguanidae) y sus implicaciones sobre la temporada de reproducción. - Méndez De La Cruz, Fausto R.; Gutiérrez Mayén, Ma. Guadalupe (Instituto de Ecología, A.C., 1991)
We studied variation in robustness of Sceloporus torquatus males and females in a population that inhabits a xeric location. Both sexes showed changes in robustness throughout the year, with lowest values present from April to June and the greatest values from November to February. There was a negative correlation between the gonadal somatic index and environmental factors and a posítive correlation between robustness index. This suggests that gonadic recrudescence was dependent on environmentai triggers and the robustness of the lizards.